Hyperspectral imaging in living and deceased donor kidney transplantation - Rasmus Wrigge; Robert Sucher; Fabian Haak; Hans-Jonas Meyer; Julia Unruh; Hans-Michael Hau; Matthias Mehdorn; Hans-Michael Tautenhahn; Daniel Seehofer; Uwe Scheuermann (BMC Medical Imaging)
Abstract Objective and background Hyperspectral imaging (HSI) is an innovative, noninvasive technique that assesses tissue and organ perfusion and oxygenation. This study aimed to evaluate HSI as a predictive tool for early postoperative graft function and long-term outcomes in living donor (LD) and deceased donor (DD) kidney transplantation (KT). Patients and methods HSI of kidney allograft parenchyma from 19 LD and 51 DD kidneys was obtained intraoperatively 15 minutes after reperfusion. Using the dedicated HSI TIVITA Tissue System, indices of tissue oxygenation (StO2), perfusion (near-infrared [NIR]), organ hemoglobin (OHI), and tissue water (TWI) were calculated and then analyzed retrospectively. Results LD kidneys had superior intraoperative HSI values of StO2 (0.78 ± 0.13 versus 0.63 ± 0.24; P = 0.001) and NIR (0.67 ± 0.10 versus 0.56 ± 0.27; P = 0.016) compared to DD kidneys. Delayed graft function (DGF) was observed in 18 cases (26%), in which intraoperative HSI showed significantly lower values of StO2 (0.78 ± 0.07 versus 0.35 ± 0.21; P < 0.001) and NIR (0.67 ± 0.11 versus 0.34 ± 0.32; P < 0.001). Receiver operating characteristic curve analysis demonstrated an excellent predictive value of HSI for the development of DGF, with an area under the curve of 0.967 for StO2 and 0.801 for NIR. Kidney grafts with low StO2 values (cut-off point 0.6) showed reduced renal function with a low glomerular filtration rate and elevated urea levels in the first two weeks after KT. Three years after KT, graft survival was also inferior in the group with initially low StO2 values. Conclusion HSI is a useful tool for predicting DGF in living and deceased KT and may assist in estimating short-term allograft function. However, further studies with expanded cohorts are needed to evaluate the association between HSI and long-term graft outcomes.